Genetic and biochemical markers in patients with Alzheimer's disease support a concerted systemic iron homeostasis dysregulation - Crespo, A.C. (2014)
Alzheimer's disease (AD) is the most common form of dementia in the elderly individuals, resulting from a complex interaction between environmental and genetic factors. Impaired brain iron homeostasis has been recognized as an important mechanism underlying the pathogenesis of this disease. Nevertheless, the knowledge gathered so far at the systemic level is clearly insufficient. Herein, we used an integrative approach to study iron metabolism in the periphery, at both genotypic and phenotypic levels, in a sample of 116 patients with AD and 89 healthy control subjects. To assess the potential impact of iron metabolism on the risk of developing AD, genetic analyses were performed along with the evaluation of the iron status profile in peripheral blood by biochemical and gene expression studies. The results obtained showed a significant decrease of serum iron, ferritin, and transferrin concentrations in patients compared with the control subjects. Also, a significant decrease of ferroportin (SLC40A1) and both transferrin receptors TFRC and TFR2 transcripts was found in peripheral blood mononuclear cells from patients. At the genetic level, significant associations with AD were found for single nucleotide polymorphisms in TF, TFR2, ACO1, and SLC40A1 genes. Apolipoprotein E gene, a well-known risk factor for AD, was also found significantly associated with the disease in this study. Taken together, we hypothesize that the alterations on systemic iron status observed in patients could reflect an iron homeostasis dysregulation, particularly in cellular iron efflux. The intracellular iron accumulation would lead to a rise in oxidative damage, contributing to AD pathophysiology.